Intersections of Language, Content, and Multimodalities: Instructional Conversations in Mrs. B's Sheltered English Biology Classroom - Carla Meskill; Jennifer Nilsen; Alan Oliveira (SAGE Publishing, 2019)
The challenges inherent in mastering academic content in a new language are many. When it comes to learning science in U.S. high schools, English learners (ELs) confront these on a daily basis. In an effort to document expert language/content instructional strategies, we analyze Mrs. B's sheltered high school biology class, made up of ELs from around the world and representing varying stages of emerging bilingualism. The aim of this 2-year case study was to detail effective teaching patterns in a high-functioning multicultural science class-a class where the myriad linguistic, cultural, and affective needs of students are expertly met-and to subsequently suggest a model for understanding and undertaking powerful language and content learning supported by multimodal referents. From a rich data set comprising class recordings, interviews, reflections from Mrs. B, course documents, student work, and survey responses emerged a model of the language/content multimodal interface for teaching ELs.